Application of principle component Analysis in differentiating the three types of Amaranthus based on their photoperiodic flowering response. Issue 1 (January 2020) - Andini, R; Sulaiman, M I; Moulana, R; Hmon, K P W; Ohsawa, R
Abstract: Response of flowering has become an attracting field for plant breeders and is pre-requisite in plant introduction process from different ecogeographical origins. Time of flowering is mostly induced by the day-length or photoperiod and temperature. Amaranth ( Amaranthus sp.) is known as multipurpose plants and utilized as grains or as vegetables. Under tropical environment, likewise in Indonesia, the requirement of day-length to induce flowering in amaranths is unrevealed as the day-length remains always constant with approximately 12 hours per day. During the introduction of amaranth to Japan, we would like to confirm the type of amaranth, which in general has been theoretically classified as short day plants. Under the variation of day-length ranging from 9 up to 15 hours during the four seasons in Japan, thus, we confirmed that amaranth as short day plants. Although, the vegetable ones required day-length up to 12 hours. Such conclusion was obtained from the flowering response of 69 accessions representing amaranth's eco-geographical variations within two consecutive years. Seeds were sown in two replicates. Plant nursery was conducted on the Norin-Ijutsu Centre belongs to the University of Tsukuba. Mean values from two replicates were obtained and the average was then further subjected to Principle Component Analysis (PCA) [JMP ver. 7.0 ( SAS Institute, USA)]. Thus, PCA was able to differentiate the flowering tendency within the three types of amaranths in the form of three ellipsoids. A post-publication change was made to this article on 11 Mar 2020 to correct the conference title in the PDF header.